Elektronejromiograficeskie issledovanija vlijanija otel'nych priemov massaza na nervno-mysecnyj apparat - Povarscenkova, Ju. A. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The purpose of the work consists in the definition of the influence of separate methods of massage on the functional condition of the segmentary device and skeletal muscles of the bottom finiteness. In the research there have taken part 16 athletes of high qualification adapted to the work on endurance, specializing in ski and bicycle races, with the experience from 8 till 11 years. The Multidirectional changes of the researched parameters under the influence of the same methods of massage testify to the action of a complex of factors in the formation of responses to the influence. The parity of these factors isn't explained only by the specificity of the action of this or that method.